THE IMPORTANCE OF HEALTH EDUCATION IN REHABILITATION VESTIBULAR - EXPERIENCE REPORT (Fiep Bulletin - online, 2014)
Introduction: The maintenance of postural balance is dependent on the integration between the visual, vestibular , somatosensory and auditory. The disharmony between these systems can lead to various disorders, as in cases of labyrinthine and vestibular dysfunction, triggering symptoms such as dizziness, vertigo, tinnitus, nausea and postural imbalances. Materials and methods: This study was developed in the physiotherapy clinic at the University of Valley of Itajaí, in Itajaí involving eleven patients with labyrinthine or vestibular dysfunction . All patients underwent an initial evaluation and later attended weekly meetings lasting 60 minutes during the first half of 2013, making a total of ten meetings. During the weekly meetings were conducted health education strategies and exercises designed to vestibular dysfunction. Results: After ten meetings we observed a decrease of complaints , mainly from bouts of dizziness and anxiety of staff, as well as greater knowledge about the labyrinthine and vestibular dysfunction. Conclusion : It was possible to verify that the knowledge about the factors that influence or trigger the labyrinthine and vestibular dysfunction associated with postural exercises and balance positively influence the daily lives of people who present labyrinthine and vestibular dysfunction .
Keywords: body balance; vestibular rehabilitation; health education .